The Effect of Adaptive Learning, Skill Agility, and Training on Teachers’ Performance in Public Junior High School in Sragi District, Pekalongan Regency - Khelly Novi Susanti; Ghufron Abdullah; Qristin Violinda (Journal of Educational Sciences, 2026)
Teachers’ performance plays a crucial role in determining the quality of education, yet it often remains inconsistent due to challenges in adapting to rapid educational changes. This study aims to examine the effect of adaptive learning, skill agility, and training on teachers’ performance in public junior high schools in Sragi District, Pekalongan Regency. A quantitative approach with a correlational design was employed. The population consisted of 173 teachers, with 121 respondents selected through proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that adaptive learning, skill agility, and training have positive and significant effects on teachers’ performance, both partially and simultaneously. Skill agility shows the strongest influence (β = 0.767), followed by training (β = 0.279) and adaptive learning (β = 0.233). The model demonstrates high explanatory power, with an R² value of 0.866, indicating that 86.6% of the variance in teachers’ performance is explained by the three variables. These findings highlight the importance of adaptive capacity and continuous professional development in improving teachers’ performance. Therefore, an integrated approach combining adaptive learning, skill agility, and training is essential to enhance teacher effectiveness in dynamic educational environments.